What has been learned about COVID‐19 vaccine hesitancy in Pakistan: Insights from a narrative review. Issue 6 (21st November 2022) - Tharwani, Zoaib Habib; Kumar, Prince; Marfani, Wajeeha Bilal; Shaeen, Sean Kaisser; Adnan, Alishba; Mohanan, Parvathy; Islam, Zarmina; Essar, Mohammad Yasir
Abstract: Background: Vaccine hesitancy is not a new phenomenon to Pakistan. This is evidenced through the slow progress of previous vaccination campaigns and programs against MMR, BCG, and especially polio. This issue continues to persist and is therefore becoming the cause of low COVID‐19 vaccination rates in Pakistan. Aim: To provide insights about COVID‐19 vaccine hesitancy among Pakistanis, and its potential harm on public health. Moreover, we aim provide recommendations to counter the factors limiting the COVID‐19 vaccination in Pakistan. Methodology: A Boolean search was conducted to find the literature in MEDLINE‐PubMed, Google Scholar, and Clinicaltrials.gov databases up till March 16, 2022. Specific keywords were used which comprised of "SARS‐CoV‐2, " "COVID‐19, " "vaccine hesitancy, " "vaccine acceptance, " "intention to vaccinate, " and "Pakistan, " with use of "OR" and "AND." Only free full‐text original studies in English language were used to compare and contrast. Results: As proven by various studies, COVID‐19 vaccination rates are influenced by multiple factors, including inaccurate beliefs about COVID‐19, hesitancy amongst healthcare workers, uncertainty regarding vaccine's efficacy and fear of side effects. Various conspiracy theories and lower testing rates among others also add up to impose a negative impact on the vaccination rates and public health of Pakistan. This may lead to newer strains of potentially harmful COVID‐19, mental health deterioration, and prolonged lockdowns. Conclusion: Vaccine hesitancy is a global public health threat, and its impacts are pronounced in Pakistan. This is reflected in the COVID‐19 pandemic; low vaccination rates in Pakistan may lead to future outbreaks of new, potentially harmful, strains of COVID‐19 which can prolong lockdowns in the country and affect mental health of the population. To improve the current situations, it is imperative for the government, educational institutes, and healthcare systems to develop trust and continually use dialogue, communication, and education to address misconceptions to improve COVID‐19 vaccination in Pakistan.